Accounting pick and paste / Wan Noor Asmuni Wan Fauzi ...[et al.] - Wan Fauzi, Wan Noor Asmuni; Ahmad, Junaidah Hanim; Wan Ahmad, Wan Noraswaniaty; Zainal Ariffin, Muhaniza; Muhamad Hanafi, Nurfazilahaini (Universiti Teknologi MARA Cawangan Kelantan, 2018)
The teaching and learning process has evolved over time. Nowadays, educators have to continuously search and develop tools to successfully engage their students in learning process, especially if the students are mature learners or very young children. Accounting Pick and Paste (APP) is an interactive learning product developed with the objective to facilitate learners who want to learn basic accounting concepts in a very simplified and fun manner. This product can help educators overcome students‟ inattentiveness problem by making lessons more enjoyable, personally interesting and motivating. Instead of merely memorising, learners would also be able to apply what they have learned during class in a more realistic way